RETRACTED ARTICLE : Asupan seng dan status seng yang rendah sebagai faktor risiko kejadian infeksi filariasis (studi kasus di kota pekalongan) - Mastuti, Dewi Nugraheni Restu (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2015)
This article has been retracted due to the multiple publications in different journalsÂ The Policy on Article retraction can be found athttps://ejournal.undip.ac.id/index.php/jgi/about/editorialPolicies#custom-0